A four-part working bibliography of neuroethics: Part 4 - Ethical issues in clinical and social applications of neuroscience - Becker, Kira (Philos Ethics Humanit Med, 2017)
BACKGROUND: As a discipline, neuroethics addresses a range of questions and issues generated by basic neuroscientific research (inclusive of studies of putative neurobiological processes involved in moral and ethical cognition and behavior), and its use and meanings in the clinical and social spheres. Here, we present Part 4 of a four-part bibliography of the neuroethics literature focusing on clinical and social applications of neuroscience, to include: the treatment-enhancement discourse; issues arising in neurology, psychiatry, and pain care; neuroethics education and training; neuroethics and the law; neuroethics and policy and political issues; international neuroethics; and discourses addressing "trans-" and "post-" humanity. METHODS: To complete a systematic survey of the literature, 19 databases and 4 individual open-access journals were employed. Searches were conducted using the indexing language of the U.S. National Library of Medicine (NLM). A Python code was used to eliminate duplications in the final bibliography. RESULTS: When taken with Parts 1-3, this bibliography aims to provide a listing of international peerreviewed papers, books, and book chapters published from 2002 through 2016. While seeking to be as comprehensive as possible, it may be that some works were inadvertently and unintentionally not included. We therefore invite commentary from the field to afford completeness and contribute to this bibliography as a participatory work-in-progress.